The shop, the dog, or the owner? Investigating the pathway of dog relinquishment in Taiwan - Wan-Jhu Huang; Gordon C. Li (Animal Welfare)
Dog relinquishment has been a persistent issue in Taiwan. The commercialisation of companion animals, inadequate regulation of pet shops and unethical breeding, and the cultural opposition to euthanasia have contributed to rising stray populations and overwhelmed shelters. However, current measures in Taiwan have focused predominantly on post-relinquishment management, with insufficient attention paid to the sources of relinquished dogs. This study examines the pathway of dog relinquishment by tracing acquisition motivation, choice of purchase channel, ownership experience, and potential relinquishment. Using an online survey of 444 Taiwanese dog owners, this study explores the interplay between these factors. While several factors relate to relinquishment, owners’ knowledge and motivations are the strongest predictors of successful ownership, as better-prepared owners tend to choose more appropriate acquisition channels, apply more effective training methods, and report fewer problem behaviours. Strengthening pre-acquisition education and tightening channel regulations may be key to reducing dog relinquishment and improving animal welfare in Taiwan.